The Influence of Eccentric Muscle Actions on Concentric Muscle Strength: An Exception to the Principle of Specificity? - Ryo Kataoka; Yujiro Yamada; William Hammert; Jun Seob Song; Witalo Kassiano; Anna Kang; Jeremy Loenneke (International Universities Strength and Conditioning Association, 2024)
The principle of specificity suggests that the largest changes in strength occur when training resembles the specific strength test. A one-repetition maximum (1RM) test, which tests the maximal concentric strength, is commonly used as a surrogate for strength adaptation. When separating muscle actions into concentric or eccentric phases, multiple lines of evidence suggest that eccentric muscle actions possess several distinct physiological properties compared with concentric actions. In accordance, there are instances where the increases in 1RM strength test were similar between eccentric-only and concentric-only resistance training. This is at odds with the principle of specificity which suggests that individuals who trained with concentric actions would be expected to have an advantage in that specific task. Although the mechanistic reasons why eccentric-biased training carries over to maximal concentric strength remains to be elucidated, the lack of discernible differences in strength gains with eccentrically-biased training (e.g., eccentric-only and accentuated eccentric training) may imply that the effects of eccentric loading in training are transferable to concentric strength. Our review revisits the role of eccentric loading in enhancing concentric maximal muscle strength. We also speculate on potential physiological factors (i.e., molecular and neural factors) that may differentiate the effects of eccentric and concentric resistance training on the changes in muscle strength. Currently, the majority of the studies investigating the changes in strength have been conducted using isokinetic eccentric training. This is important as there is a viewpoint that the magnitude of chronic adaptations with different modalities of eccentric exercises (i.e., isotonic, isokinetic, and isoinertial training) may also differ from each other. While it has been suggested that eccentric action has a greater transferable capacity for strength adaptations compared to concentric actions, future investigations are warranted to investigate with different modalities of eccentric exercises. There also remains a host of unanswered questions related to the role of eccentric action for maximal concentric strength. For example, future studies may examine whether the eccentric action would be additive when the training is already maximally loaded during the concentric action for increasing concentric maximal strength. We suggested a few different designs that could be used to answer some of these questions in future studies.